The volume of euro coins held for transaction purposes in Germany - Markus Altmann; Nikolaus Bartzsch (Research On Money in the Economy (ROME), 2014)
According to estimates using the seasonal method, the volume of euro coins held for transaction purposes in Germany in 2011 stood at exteuro2.3 billion; this corresponds to around 36% of the total volume of German (ie issued by the Deutsche Bundesbank) euro coins in circulation. 76% of the total volume of coins held for transaction purposes was accounted for by exteuro1 and exteuro2 coins. Only in the case of exteuro2 coins has the cash stock held for transaction purposes made a significant contribution to the growth in the volume of coins in circulation in recent years. Therefore, structural models are the most suitable method of determining the demand for this denomination. Given the overall weakness in the growth of the cash held for transaction purposes, coin processing costs have, all other things being equal, risen less sharply than the volume of coins in circulation. Small denomination coins (1 and 2 cent coins) account for comparatively low shares of the coins held for transaction purposes (less than 30%). This is because they are hoarded to a greater extent in order to lighten one's wallet or purse, or are lost. This could be used as an argument for applying a rounding rule (to nearest five cents). It is presumed that abroad German euro coins are, on balance, only held outside the euro area. There they are being hoarded on a permanent basis. Due to the inadequate data availability, the cash balance held for domestic transactions by sector cannot be fully recorded. Estimates for 2011 put them at between exteuro0.7 billion and exteuro1.0 billion. Households and credit institutions accounted for the largest share.
Keywords: E41; E42; 330; coins; transaction balance; hoarding; foreign demand; seasonal method; introduction of euro cash